Control of swine enzootic pneumonia by spraying organic acids in fatteners’ buildings - MICHI (Κ. ΜΙΧΗ) K.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; RODI-BOURRIEL (Α. ΡΟΔΗ-BURRIEL) A.; CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ) G. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this study, the possibility to control enzootic pneumonia by spraying mild organic acids in fatteners’ buildings was investigated. In a farm with enzootic pneumonia, two groups, each of 120 weaned pigs, were housed in 2 separate rooms. With the pigs inside, the rooms were being sprayed once a week, for a total period of 20 weeks (up to the end of fattening period), either with a mixture of organic acids (1st room= AML-pigs), or with water (2nd room= placebo control pigs). Groups were compared with each other with respect to pigs’ health status, mortality, performance parameters (average daily gain, feed conversion ratio) and the presence of specific lesions and pathogens in their lungs. It was shown that the incidence of coughing and the mortality in the AML-pigs were lower (10% and 3.25% respectively) compared to placebo controls (25% and 8.26% respectively). At the age of 70,120 and 165 days, the AML-pigs were 1.9 kg, 2.85 kg and 4.75 kg heavier, respectively, compared to controls (P< 0.001). Also, the pigs of the acid treated group have performed better than the controls with respect to average daily gain (674 g and 640 g respectively) and feed conversion ratio (3,00 and 3,14 respectively) (P<0.05). Lung lesions, characteristic for enzootic pneumonia, were detected in 37.5% of the AML-pigs and in 57.5% of placebo controls. Bacteria in the lungs, possibly complicating the disease, were isolated from more pigs of the control group compared to the acid-treated group. Finally, no clinical side effects following each application of the product were observed. The results of the present study show that, spraying of mild organic acids in a Mycoplasma hyopneumoniae-affected pig farm can be used for controlling the disease and improving performance parameters.